Upaya Karang Taruna dalam Pengelolaan Objek Wisata Air Te Rjun Luahandroi di Desa Fulolo Kecamatan Alasa Kabupaten Nias Utara - Cari Nosta Adil Laoli; Ade Putra Arif Panjaitan; Liyus Waruwu; Yulia Kurnia Sari Sitepu; Masniar Sitorus (Jurnal Ilmu Sosial dan Humaniora, 2025)
Tourism plays a vital role in improving the local economy. This study, entitled "The Efforts of Karang Taruna in Managing the Luahandroi Waterfall Tourist Attraction in Fulolo Village, Alasa District, North Nias Regency," aims to determine the role of Karang Taruna in managing the tourist attraction and the strategies employed. The research method employed a descriptive qualitative approach with interview, observation, and documentation techniques. The results indicate that Karang Taruna plays an active role through collaboration with the community, utilization of public facilities, promotion through social media, and mutual cooperation activities. These efforts have had a positive impact on tourism development and improving the economy of the Fulolo Village community.